2021
DOI: 10.1021/acs.jafc.1c01634
|View full text |Cite
|
Sign up to set email alerts
|

Fine-Tuning of Process Parameters Modulates Specific Metabolic Bacterial Activities and Aroma Compound Production in Semi-Hard Cheese

Abstract: The formation of cheese flavor mainly results from the production of volatile compounds by microorganisms. We investigated how fine-tuning cheese-making process parameters changed the cheese volatilome in a semi-hard cheese inoculated with Lactococcus (L.) lactis, Lactiplantibacillus (L.) plantarum, and Propionibacterium (P.) freudenreichii. A standard (Std) cheese was compared with three variants of technological itineraries: a shorter salting time (7 h vs 10 h, Salt7h), a shorter stirring time (15 min vs 30 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…The same correlation was observed for OA profile-hard cheese contained low amounts of OA, while semi-hard and soft cheeses were rich in organic acids, suggesting the intensive metabolic processes of LAB genera presented there (Figure 2). Concentrations of lactate, acetate, propionate, butyrate, succinate and citrate were similar to values, estimated for cheeses of the same stages of ripening [53]. Lactate and acetate were the major products of fermentation followed by succinate and citrate, the latter was regarded as a substrate for succinate production by lactobacilli [54,55].…”
Section: Discussionsupporting
confidence: 81%
“…The same correlation was observed for OA profile-hard cheese contained low amounts of OA, while semi-hard and soft cheeses were rich in organic acids, suggesting the intensive metabolic processes of LAB genera presented there (Figure 2). Concentrations of lactate, acetate, propionate, butyrate, succinate and citrate were similar to values, estimated for cheeses of the same stages of ripening [53]. Lactate and acetate were the major products of fermentation followed by succinate and citrate, the latter was regarded as a substrate for succinate production by lactobacilli [54,55].…”
Section: Discussionsupporting
confidence: 81%
“…The biochemical changes among diverse complex microbial communities involve the conversion of milk fat, carbohydrate, and protein to a very wide range of flavor compounds by three principal metabolic pathways, lipolysis, glycolysis, and proteolysis [ 68 ]. These pathways require several different enzymes that can be obtained from milk endogenous enzymes, clotting enzymes, and ripening microbial enzymes [ 69 ]. Cheeses produced from raw milk generally exhibit a more complex microbiota than cheeses made of pasteurized milk; as a consequence, a large quantity of aromatic compounds has been found in raw milk cheeses [ 70 ].…”
Section: Significance Of Arthrobacter Spp In the D...mentioning
confidence: 99%
“…Among the microorganisms found on the surface of cheeses, a small number have been evaluated for their ability to produce flavor compounds, especially bacteria belonging to the genus Arthrobacter . Several strains of A. arilaitensis isolated from French smear-ripened cheeses were used to study the production of volatile aroma compounds, and it was found that various volatile compounds, e.g., aldehydes, esters, ketones, alcohols, and sulfur compounds, were produced by two strains, A. arilaitensis Mu107 and A. arilaitensis Po102 [ 69 ]. In a comparison study in lab-produced cheese between a typical old-young starter and a defined starter consisting of fungi and bacterial strains, a strain isolated from German Tilsit cheese, A. nicotianae , was the most important in the development of a typical smell—a sulfury volatile flavor [ 41 ].…”
Section: Significance Of Arthrobacter Spp In the D...mentioning
confidence: 99%
“…Its preparation includes the addition of Streptococcus thermophilus as a starter strain that reduces the pH and induces the growth of inoculated Lactobacillus helveticus (Baptista et al, 2018). The proteinases and peptidases produced by these lactobacilli play an important role in the breakdown of casein during cheese fermentation and ripening, contributing to the synergistic growth of the strains of S. thermophilus and L. helveticus (Hayaloglu, 2016) and allowing the development of the flavor (Cao et al, 2021). In addition, propionic fermentation is responsible for the holes inside the cheese through CO 2 production and its mild flavor (Hu, 2012;Fox and Guinee, 2013).…”
Section: Introductionmentioning
confidence: 99%